Tpack-Based Multimodal Literacy In English Narrative For Um Tapsel Information Technology Students - Shofie Nisma Dewi; Khairunnisah Khairunnisah; Ahmad Tarmizi; Novita Manja Sari; Solidha Ramadiah (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
Multimodal literacy based on TPACK (Technological Pedagogical Content Knowledge) is an educational approach that integrates technology with pedagogical and content knowledge to develop multimodal literacy in students. Multimodal literacy refers to the ability to understand, analyse, and produce texts that combine various modes of communication such as written text, images, sound, video, and interactivity. Focus of this research is to find out TPACK-based multimodal literacy in improving English narratives for IT students of UM-Tapsel. English narrative is a form of writing or conversation that tells an event or series of events in English. The main purpose of narration is to tell a story or explain an event in detail, giving a clear picture of what happened, who was involved, when and where the event occurred, as well as how and why the event occurred. In addition, the purpose of this study is to find out the perspectives and levels of mutilmodal literacy of students in English narratives.The method used in this research is qualitative in the form of a case study. The sample size is 40 students of Faculty of Science and Technology, Information Technology study programme. Questionnaires were used to collect data in this study.